Structural studies of NaPO3-MoO3 glasses by solid-state nuclear magnetic resonance and raman spectroscopy - Santagneli, Silvia H.; de Araujo, Carla C.; Strojek, Wenzel; Eckert, Hellmut; Poirier, Gael; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP] (Amer Chemical Soc, 2007)
Vitreous samples were prepared in the (100 - x)% NaPO3-x% MoO3 (0 <= x <= 70) glass-forming system by a modified melt method that allowed good optical quality samples to be obtained. The structural evolution of the vitreous network was monitored as a function of composition by differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT-IR), Raman scattering, and solid-state nuclear magnetic resonance (NMR) for P-31, Na-23, and Mo-95 nuclei. Addition of MoO3 to the NaPO3 glass melt leads to a pronounced increase in the glass transition temperatures up to x = 45, suggesting a significant increase in network connectivity. For this same composition range, vibrational spectra suggest that the Mo6+ ions are bonded to some nonbridging oxygen atoms (Mo-O- or Mo=O bonded species). Mo-O-Mo bond formation occurs only at MoO3 contents exceeding x = 45. P-31 magic-angle spinning (MAS) NMR spectra, supported by two-dimensional J-resolved spectroscopy, allow a clear distinction between species having two, one, and zero P-O-P linkages. These sites are denoted as Q(2Mo)((2)), Q(1Mo)((2)), and Q(0Mo)((2)), respectively. For x < 0.45, the populations of these sites can be described along the lines of a binary model, according to which each unit of MoO3 converts two Q(nMo)((2)) sites into two Q((n+1)Mo)((2)) sites (n = 0, 1). This structural model is consistent with the presence of tetrahedral Mo(=O)(2)(O-1/2)(2) environments. Indeed, Mo-95 NMR data suggest that the majority of the molybdenum species are four-coordinated. However, the presence of additional six-coordinate molybdenum in the MAS NMR spectra indicates that the structure of these glasses may be more complicated and may additionally involve sharing of network modifier oxide between the network formers phosphorus and molybdenum. This latter hypothesis is further supported by Na-23{P-31} rotational echo double resonance (REDOR) data, which clearly reveal that the magnetic dipole-dipole interactions between P-31 and Na-23 are increasingly diminished with increasing molybdenum content. The partial transfer of modifier from the phosphate to the molybdate network former implies a partial repolymerization of the phosphate species, resulting in the formation of Q(nMo)((3)) species and accounting for the observed increase in the glass transition temperature with increasing MoO3 content that is observed in the composition range 0 <= x <= 45. Glasses with MoO3 contents beyond x = 45 show decreased thermal and crystallization stability. Their structure is characterized by isolated phosphate species [most likely of the P(OMo)(4) type] and molybdenum oxide clusters with a large extent of Mo-O-Mo connectivity.